Brejčev drugi mandat - Rahten, Andrej (Studia Historica Slovenica, 2021)
The article deals with the main political challenges of the Provincial Government for Slovenia led by Janko Brejc, one of the most prominent Slovene political leaders in the post-imperial transition era. Based on the archival sources and different press reports, the article presents the crucial political developments in Slovenia in 1920, during Brejc’s second term as the provincial prime minister, especially the April strike and the Carinthian Plebiscite.
Keywords: 1920; Aleksander Karađorđević; Avstrija; Brejc, Janko; Carinthian Plebiscite; Gregor Žerjav; Janko Brejc; Karađorđević, Aleksandar I; koroški plebiscit; politična zgodovina; Slovene People’s Party; Slovenija; Slovenska ljudska stranka; Žerjav, Gregor